Regulation of apoptosis by Bcl‐2 family proteins - Burlacu, Alexandrina (J Cell Mol Med, 2007)
For multicellular organisms, the rigorous control of programmed cell death is as important as that of cell proliferation. The mechanisms involved in the regulation of cell death are not yet understood, but a key component is the family of caspases which are activated in a cascade and are responsible for the apoptotic‐specific changes and disassembly of the cell. Although the caspases represent a central point in apoptosis, their activation is regulated by a variety of other factors. Among these, Bcl‐2 family plays a pivotal role in caspases activation, by this deciding whether a cell will live or die. Bcl‐2 family members are known to focus much of their response to the mitochondria level, upstream the irreversible cellular damage, but their functions are not yet well defined. This review summarizes the recent data regarding the Bcl‐2 proteins and the ways they regulate the apoptosis.